Youngsters, law-breaking and educational practices: paradoxes of the biopolitics and social control (2008)
This article helps to understand the current forms of government on young people in Bogotá, particularly on those young offenders of the law, who are subjects to be controlled through a series of rehabilitation programs, reeducation and socialization; usually based on religious, scientific and commercial ideas. At the end, the article proposes other ways of understanding the contemporary young subjectivities, the educational care practices and the socio-professional practices by social workers, involved the social issues of young people in our country.